The inheritance and durability of scab resistance in apple progenies - Tóth, M.; Pedryc, A. (International Journal of Horticultural Science, 2005)
In order to select the appropriate parent cultivars and maintain the durability of resistance, it is important to clarify the mechanisms of inheritance of scab resistance depending on the parents. It has been known that the progeny segregation ratios based on scab-resistance do not depend only on the genotype of the resistance locus but also on the genetical makeup of the donor and recipient parents as well as on the susceptible parent.The aim of this study has been to demonstrate what factors in the Vf, Vr and VA scab-resistant cultivars — combined with susceptible and resistant parents — affect the inheritance and durability of resistance in seedlings in their first 4 year's growing four years' growth. After inoculating apple seedlings sown in 2001 with the suspension of Venturia inaequalis (Cke.) Wint. in the greenhouse, we studied the segregation ratios of the progenies into reaction classes. Seedlings showing resistance in the greenhouse were also evaluated for scab-resistance after they had been moved to the field and had naturally been infected with the pathogen in 2002 and 2004.The majority of our results obtained in the greenhouse test, similarly to earlier experiences, have not justified monogenic inheritance at the phenotypic level. The effect of susceptible parent cultivars on the segregation ratio of progenies have become apparent again. The high infection rate of seedlings in the field trials, which had previously exhibited varying degrees of resistance in the greenhouse test, has raised concern. Our data has raised further doubts, concerning the durability of Vf resistance in Hungary. It is assumed that the composition of natural field populations of Venturia inaequalis in Szigetcsép has changed. The complexity of Vf resistance has been confirmed. The high infection rate in the progenies derived from Vf resistant cultivars draws the attention to the importance of utilizing additional sources of resistance.